2008
DOI: 10.1007/s00464-008-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy in pregnant patients: a review of 45 cases

Abstract: This large series from a single institution shows a low rate of preterm delivery and absence of foetal loss after laparoscopic appendectomy. Regardless of trimester, the low rate of complication makes it a valuable option for pregnant patients with suspicion of acute appendicitis. The rate of normal appendectomies remaining high, efforts have to be made towards new diagnostic modalities to lower the negative appendectomy rate in this specific population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 19 publications
1
52
1
13
Order By: Relevance
“…The mean age of the patients was 26 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years. The mean gestational age at the time of LA was 17.6 weeks (4-33 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patients was 26 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years. The mean gestational age at the time of LA was 17.6 weeks (4-33 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] We operated 10 patients within 12 hours with laparoscopic approach. We used open technique for the first trocar insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review by Walsh et al (2008) found significantly high foetal loss (6 %) but lower preterm delivery rate [15]. Systematic review and meta-analysis by Wilasrusmee et al (2012) [17].…”
Section: Appendicitismentioning
confidence: 95%
“…Laparoscopy has been found to be safe in any trimester [18], but LA was associated with longer operating time and higher conversion rates in the third trimester [17].…”
Section: Appendicitismentioning
confidence: 99%
“…The ongoing debate is whether the laparoscopic procedure leads to a higher percentage of fetal loss as is reported in a systematic review from the UK (Walsh et al, 2008) or not, as is stated in a review from the United States (Jackson et al, 2008). More recent studies consider the laparoscopic approach to be safe and effective with a low rate of complications for the mother and the fetus (Corneille et al, 2010;Jeing et al, 2011;Kirshtein et al, 2009;Lemieux et al, 2009;Machado et al, 2009;Moreno-Sanz, 2007;Sadot et al). It has to be stated that long-term consequences of the pneumoperitoneum for the fetus have not yet been studied.…”
Section: Pregnant Patientsmentioning
confidence: 99%